The Analysis Of The Effect Of Air Leakage In The Pneumatic System Of A 450 Hp Carrier Rig On Drawwork Performance: Analisis Pengaruh Kebocoran Udara Pada Sistem Pneumatic Rig Carrier 450 Hp Terhadap Kinerja Drawwork - Riau Anggoro Trisno; Mohammad Anshori; Aprillia Dwi Ardianti (Universitas Pendidikan Ganesha, 2026)
The pneumatic system plays a crucial role in operating the drawworks, which is a key component in drilling operations. One common problem is air leakage, which leads to pressure drops and negatively affects the drawworks' performance, particularly in response time. The study uses a paired sample t-test method to compare air pressure and response time under normal conditions and during leakage. The results show an average pressure drop of 41–42 psi and an increase in response time by approximately 35–36 seconds under leakage conditions. Additionally, a simulation using Autodesk Inventor revealed significant pressure losses at hose connections and solenoid valves. These findings indicate that air leakage has a significant negative impact on the efficiency and performance of the pneumatic system, especially in the operation of the drawworks.